Deskripsi Program Sekolah Dasar Islam Terpadu di Kota Pontianak dalam Menumbuhkan Nilai Karakter Religius - Aisah Ningrum; Suparjan Suparjan; Rio Pranata (PALAPA, 2022)
This study aims to describe the program carried out by SDIT in the city of Pontianak in fostering religious character values. The method that has been used in this research is descriptive qualitative with interview and documentation techniques. This research focuses on the program carried out by the school in growing religious character values from the planning stage to its implementation. Based on the results of the research, there were 10 programs carried out by SDIT in the city of Pontianak in fostering religious character values such as praying, reading the Al-Qur’an before studying, integrating religious values in subjects, infaq/alms, congregational dzuhur prayers, muraja`ah, quick Islamic boarding schools, Mabit , Parenting Seminar class outing, and tahfidz Qur’an. Program planning is compiled through the school's vision and mission, lesson plans, and is also planned by setting it up in the academic calendar. Meanwhile, the implementation of the program has been carried out based on the program principles, namely comprehensively, comparatively, continuously, and functionally. So it can be concluded that in fixing and shaping the character of students towards a better direction, it can be done through education. One of them is by implementing programs that have been designed by schools with the aim of growing the character of students, especially their religious character, because religious character is the main character that acts as a supporter in character education